Perbedaan Perbankan Syariah dengan Konvensional - Wahyuna, Sari; Zulhamdi, Zulhamdi (Al-Hiwalah: Journal of Sharia Economic Law, 2022)
This article aims to test the financial performance between Islamic Banks and Conventional Banks, and examine the influence of financial performance on investment decisions, both in Islamic Banks and Conventional Banks. Basically it has a function as a place to collect funds from the public in the form of savings and distribute them again to the community in the form of credit or other forms in order to improve the standard of living of the people as explained in Law Number 10 of 1998 concerning Banking, so that today's society many use banking services in Indonesia, but many Indonesian people are now starting to hesitate to use banking services, especially conventional banking because it adheres to the interest system which according to Islam is forbidden. As an alternative for people who are afraid of bank interest, Islamic banking is born which applies a profit-sharing system in calculating the profits of its funds and based on Islamic law is recognized as halal. Differences Islamic Banks and Conventional Banks:. Sharia banking law is based on Islamic sharia based on the Qur'an and Hadith and Fatwa Ulama (MUI) while conventional banks are legal based on positive law applicable in Indonesia (Civil and Criminal). violates Islamic law (only for halal businesses) while lending to conventional banks can be done in various businesses that are considered safe and profitable. As long as it doesn't violate applicable laws and regulations